2021
DOI: 10.3390/en14238083
|View full text |Cite
|
Sign up to set email alerts
|

Pitch Control of Three Bladed Large Wind Energy Converters—A Review

Abstract: Modern multi-megawatt wind turbines are currently designed as pitch-regulated machines, i.e., machines that use the rotation of the blades (pitching) in order to adjust the aerodynamic torque, such that the power is maintained constantly throughout a wide range of wind speeds when they exceed the design value (rated wind speed). Thus, pitch control is essential for optimal performance. However, the pitching activity is not for free. It introduces vibrations to the tower and blades and generates fatigue loads. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 134 publications
0
6
0
Order By: Relevance
“…The authors also found that by combining fuzzy systems, neural networks, and search algorithms, they could build diffuse neural networks with evolutionary capabilities to implement and represent human thoughts in pitch-controlled systems effectively. Following this, a complete review of the collective and individual pitch control, damping control, and pitch actuator control of large-scale wind energy converters was investigated in [83]. However, these reviews have not focused broadly on investigations into the coordinated pitch/yaw and generator torque control of super-large WTSs.…”
Section: Recent Pitch Yaw and Torque Control Methods For Super-large ...mentioning
confidence: 99%
“…The authors also found that by combining fuzzy systems, neural networks, and search algorithms, they could build diffuse neural networks with evolutionary capabilities to implement and represent human thoughts in pitch-controlled systems effectively. Following this, a complete review of the collective and individual pitch control, damping control, and pitch actuator control of large-scale wind energy converters was investigated in [83]. However, these reviews have not focused broadly on investigations into the coordinated pitch/yaw and generator torque control of super-large WTSs.…”
Section: Recent Pitch Yaw and Torque Control Methods For Super-large ...mentioning
confidence: 99%
“…The control signal, which is applied to all pitch actuators, is the pitch angle (pitch demand), and the feed-backed signal is the generator rotational speed. The rated generator rotational speed serves as the set-point (see [35] for a review). The main challenge is that very few inputs (only the three blade pitch actuators) are available for all control functions, so different control objectives are normally contradictory, and a compromise is required.…”
Section: The Control Problemmentioning
confidence: 99%
“…In variable-speed, variable-pitch machines, the rotational speed, and the grid frequency are decoupled due to an indirect connection between generator and grid, which is carried out, nowadays, by the so-called back-to-back converters [48]. This concept is about 25 years old and allows wind turbines to down-regulate by reducing their speed while the grid frequency is maintained.…”
Section: Individual Wind Turbine Controlmentioning
confidence: 99%